THE CURRENT STATE OF DEVELOPMENT OF INSURANCE COMPANIES ON THE BASIS OF COMPETITION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This scientific article examines the current state of insurance activity and trends in development based on competition. Several problems of competition between insurance companies in the insurance market have been analyzed and a number of solutions have been proposed.